Developing Adequate Self-Esteem in Primary School Students Through Innovative Educational Practices - Zhubakova, Saule; Makhambetova, Zhamilya; Dyusenbayeva, Bibigul; Baіmenova Botagoz; Temirov, Kuanysh (Pedagogy and Psychology, 2025)
The study discusses the features of developing adequate self-esteem in primary school students, addressing this crucial aspect of their successful adaptation and development during a critical period when children actively compare themselves with others and evaluate their achievements and failures. Methodology and Methods. The research employs theoretical analysis of cognitive, emotional, and social development processes in primary school age, examining the dynamic relationship between self-esteem formation and various developmental factors. The study includes analysis of assessment methods and pedagogical strategies for supporting individual student achievements. Results. The development of adequate self-esteem in primary school students was identified as a dynamic process closely related to their cognitive, emotional, and social development, directly affecting their self-image formation. The crucial role of teachers in developing adequate self-esteem was established, with practical recommendations developed for creating favorable classroom atmosphere and implementing appropriate assessment methods. Problems associated with both low and high self-esteem were identified, and corrective strategies for addressing negative attitudes were formulated. Scientific novelty. The research provides a comprehensive theoretical framework for understanding self-esteem development in primary school students, establishing the interconnected nature of cognitive, emotional, and social factors in this process and emphasizing the need for an integrated approach including parental involvement and psychological support. Practical significance. The study offers practical recommendations for teachers, psychologists, and parents interested in promoting harmonious development of primary school students, providing specific strategies for classroom management, assessment practices, and corrective interventions to foster adequate self-esteem formation.